Gender and social policy in Turkey: positive discrimination or a second-class female citizenship? - Kılıç, Azer. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
This thesis examines the gender-specific provisions of social security and labor legislations in Turkey. The development of the gendered policies in question is traced back through the modern history of Turkey, focusing on normative amendments in the legislation and the related discourses of the policy-making elites on the base of parliamentary discussions. The thesis aims to explore the gender norms and relations which are embedded in the policies pointing at the conceptualizations and assumptions on gender roles, family structure, parental responsibility, sexual division of labor, etc. signified by the policies and discourses. This analysis revolves around the main question of the thesis, that is, whether the specific benefits and "protections" provided to women mean a positive discrimination to satisfy specific needs and to compensate disadvantages and so, to facilitate women̕s equal participation in society, or they reinforce the underlying gender norms and relations which define needs in gendered terms and create gender injustice, leading to a second-class citizenship for women. Despite the variety of discourses and policy-areas, the thesis argues that the underlying common assumptions and principles represent women as a weaker, vulnerable group in need of special protection and largesse, stigmatizing them as "the destitute." The regulations reinforce the conditions of familial dependency and the gendered division of labor both in the domestic sphere and paid employment, confining women to traditional gender roles. However, recently some normative changes also have been observed in the policies, which can be interpreted as promising for the transformation of existing gender relations.
Keywords: Women -- Turkey -- Social conditions.